The Adaptive Capacity of Mangrove Ecosystem in the Sub-District Sungai Apit, Siak Regency, Riau Province - Adriman Adriman; Eko Prianto; Romie Jhonnerie; Nur El Fajri (Jurnal Perikanan dan Kelautan, 2023)
This research was conducted for five months from May to September 2022 which is located in Sungai Apit District by taking six (6) villages as sampling locations from the eight (8) existing villages. This research was conducted for five months from May to September 2022 which is located in Sungai Apit District by taking six (6) villages as sampling locations from eight (8) existing villages. The research objective was to calculate and assess the adaptive capacity of mangrove ecosystems in Siak District, Siak Regency. Measurement of the adaptive capacity of mangrove ecosystems is carried out by analyzing six parameters, namely Mangrove Dimension Index (IDMg), Dominant Mangrove Species, Mangrove Tree Density, Number of Mangrove Species, Substrate Type, Ecosystem Distance from Settlement. The value of the adaptive capacity of mangrove ecosystems is in the range of 0.0-1.0, with five capacity categories namely "very low, low, medium, high, and very high". The results showed that the number of mangrove species found growing on the coast of Sungai Apit District was 19 species belonging to 10 families and 12 genera, distributed in the "low" category with a mangrove dimension index (IDMg) value of 0.6 (0.4<IDMg <0.8).Dominant species from the Rhizophoraceae family with a density classified as "high". The adaptive capacity of the mangrove ecosystem at the study site is classified as ", high" with an adaptive capacity value of 0.67 (0.6 ≤ KPMg ≤ 0.8)